Fluid balance during taekwondo training - Belfort, F. G.; dos Santos Amorim, P. R.; Silva, C. E.; Gonçalves, C. F. F.; Niquini, P. R.; Silva, R. P.; Marins, J. C. B. (Revista Brasileira de Medicina do Esporte, 2021)
Introduction; Dehydration has been described as one of the main factors of reduced performance in combat sports activities, leading to death in extreme cases. Objective: To investigate the pre-training hydration status and changes in fluid homeostasis during two taekwondo training sessions. Methods: Eighteen male college athletes (age 22.6 ± 3.37 years) were assessed. The study design aimed to reproduce the conditions of a 90-minute taekwondo training session, divided into three stages: a) warm-up exercises (20 min); b) poomsae (30 min) and c) technical training (40 min). The athletes had ad libitum water intake during training. To assess the hydration status we considered body mass (BM), the amount of liquid consumed and urine output, which enabled us to establish absolute and relative fluid loss in kg and percentage as well as the sweating rate. We also considered urine specific gravity (USG), urine color (U-COL), and subjective sensation of thirst (Sthirst) before and after the training session. Pre- and post-training results were compared separately in each session and between sessions. Results: There was a significant difference (P<0.05) in pre-training BM between the two days of training. There was a significant difference (P<0.05) in the final BM on both days of the experiment. Most subjects had relative dehydration below 2%. A significant difference (P<0.05) was recorded pre and post training for U-COL and Sthirst, with the highest rates obtained at the end of each session. Participants always started training at a low dehydration status (USG >1,020g.ml-1). Conclusions: The athletes tended to start the training sessions in dehydration status, which increases over the course of the training. Ad libitum water intake was not sufficient to balance fluid loss. Changes in fluid levels between sessions were similar.